La actividad en España del obispo de Michoacán y de Tlaxcala Antonio Ruiz de Morales - Paniagua Pérez, Jesús (1994)
This article is intended to offer a preview of the work and character of Antonio Ruiz de Morales. This sixteenth century figure, a noted humanist who attained great fame in his day, was a cleric in the Order of Santiago (Saint James). Thanks to his merits, he was appointed Bishop, first of Michoacán and latert of the Diocesis of Puebla-Tlaxcala. We are currently engaged in preparing an edition of his works, which show the intellectual worth of this prelate, who had very close connexions with the leading lights of the intelligentsia of his times, such as Benito Arias Montano, Jerónimo Gudiel, Ambrosio de Morales, and others.
Queremos con este trabajo dar comienzo al rescate de la vida y la obra de un humanista español del siglo XVI, muy ligado a la ciudad de León, que inició su actividad episcopal en Pátzcuaro y acabó sus días al frente de la diócesis mexicana de Puebla-Tlaxcala. Poco se sabe de él hasta el momento, a pesar de la importancia que tuvo en su tiempo, y este trabajo no pretende ser más que un pequeño adelanto para una posterior investigación que hemos abierto en dos frentes: en México y en España, lugares en los que discurrió la vida de este hombre.
Keywords: Ruiz de Morales y Molina, Antonio, -- - 1576?; Obispos -- Michoacán (México, Estado) -- Tlaxcala (México, Estado)